In quest for Malaysian healthcare space standards: Are we any different? - Labour Delivery Rooms as bases for comparative study - Mohd Nawawi, Norwina (2009)
UK, Australian and US standards has been used as basis for Malaysian healthcare standards revised over time. Towards a caring healthcare environment for Malaysian, the Ministry of Health Malaysia had formed several committees within its organisation and affiliated ministry as well as the healthcare industry to set a truly Malaysian Standard for Malaysian. For this research, Labour Delivery Room (LDR) has been chosen as the case study in view of its purpose to assist in the natural process of birthing that normally happened at home among relatives and birth attendant which are now being carried out in a man-made hospital environment by government midwifes and doctors. Birthing as a socio-cultural process involving family members and certain rituals for ease of birth, hypothetically requires more than just clinical settings. Towards humanizing the space for its purpose, the needs of patient, clinical staff, technical/ maintenance staff and relatives as users of the space should be the criteria in assessing its human-effectiveness. However due to limitation of time, this study can initially compare the LDRs provided within existing selected Malaysian public healthcare facilities in terms of area, space configuration, usability (clinical procedure) and physical environment. Through questionnaire surveys with traditional birth attendants and local population (young and elderly mothers), literature review and observations, hypothetically a basic criteria on “humane environment for Malaysian LDR’ could be formulated. This criterion will be used to gauge existing local LDRS of its caring environment before comparison to international standards for any significant differences could be made. The outcome of this research shall be a step towards realising the necessary ingredients towards a humane environment not only in LDR design but in many other healthcare spaces for Malaysian.